2003
DOI: 10.1046/j.1523-1747.2003.12562.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Melanoblasts in Culture: Expression of BRN2 and Synergistic Regulation by Fibroblast Growth Factor-2, Stem Cell Factor, and Endothelin-3

Abstract: The BRN2 transcription factor (POU3F2, N-Oct-3) has been implicated in development of the melanocytic lineage and in melanoma. Using a low calcium medium supplemented with stem cell factor, fibroblast growth factor-2, endothelin-3 and cholera toxin, we have established and partially characterised human melanocyte precursor cells, which are unpigmented, contain immature melanosomes and lack L-dihydroxyphenylalanine reactivity. Melanoblast cultures expressed high levels of BRN2 compared to melanocytes, which dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
117
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(128 citation statements)
references
References 71 publications
(83 reference statements)
11
117
0
Order By: Relevance
“…We have excluded SNAIL and ETS-1 as responsible factors for regulating CDH13 expression (data not shown). This study focused on whether CDH13 promoter activity might be under the control of transcription factor BRN2, based on the in silico detection of consensus binding sequences of BRN2 in the proximal promoter region of CDH13, on observations of increased levels of BRN2 [12][13][14][15][16] and decreased levels of T-cadherin 9 expression in melanomas, and on observations of opposing effects of BRN2 [12][13][14][15][16] and T-cadherin 9 on melanoma cell behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have excluded SNAIL and ETS-1 as responsible factors for regulating CDH13 expression (data not shown). This study focused on whether CDH13 promoter activity might be under the control of transcription factor BRN2, based on the in silico detection of consensus binding sequences of BRN2 in the proximal promoter region of CDH13, on observations of increased levels of BRN2 [12][13][14][15][16] and decreased levels of T-cadherin 9 expression in melanomas, and on observations of opposing effects of BRN2 [12][13][14][15][16] and T-cadherin 9 on melanoma cell behavior.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 BRN2 expression is upregulated in melanoma cell lines and in melanoma lesions where cells expressing high levels of BRN2 show enhanced invasive and metastatic capacity. [12][13][14][15][16] Silencing of BRN2 in melanoma cell lines reduces proliferation, invasion and tumorigenesis. [14][15][16][17] In contrast, silencing of T-cadherin in melanocytes increases invasive capacity, whereas ectopic re-expression in several T-cadherin-deficient melanoma cell lines reduces attachment-independent growth, migration and invasion in vitro and also their tumorigenicity in vivo.…”
mentioning
confidence: 99%
“…POU3F2 also plays a role in the production and positioning of neocortical neurons (Sugitani et al, 2002). In addition to the nervous system, several studies have reported that POU3F2 is expressed in normal melanocytes and is upregulated in malignant melanoma cells where its expression is regulated by the Wnt/-catenin and activated BRAF signalling pathways (Cook et al, 2003;Eisen et al, 1995;Goodall et al, 2004a;Goodall et al, 2004b;Thomson et al, 1995). However, POU3F2 has not yet been selectively inactivated in the melanocyte lineage and genetic dissection of its role in normal melanocyte physiology and in melanoma will be a welcome and important addition to the field.…”
Section: Pou3f2 An Activator and A Repressor Of Critical Target Gementioning
confidence: 99%
“…There is also evidence that c-Kit, tyrosinase and TRP-1 gene expression are coordinated in melanocytes [55]. In vitro studies have shown that TPA (PMA) induces neural crest cell differentiation into melanocytes and stimulates proliferation and differentiation of normal melanocytes [24,56]. Similarly, in our culture system, the addition of cholera toxin and PMA to the Mel- It has been reported that withdrawal of cAMP inducers (CT+IBMX) from the medium in melanocyte cultures causes cells to become senescent [57].…”
Section: Discussionmentioning
confidence: 99%
“…Examination of melanoblasts is important to analyze basic mechanisms of cell differentiation, and to study the pathomechanisms of melanoma and genetic disorders of melanocyte development [24].…”
Section: Role Of C-kit and Tyrosinase-related Proteins In Regulation mentioning
confidence: 99%